Petrogenesis and tectonic environment of the Middle Permian Luerma igneous complex in the southern Lhasa subterrane, Tibet: Evidence from geochemistry; Rb–Sr, Sm–Nd, and Lu–Hf isotopes; and zircon U–Pb geochronology - Liu, Hong; Li, Guangming; Li, Wenchang; Ma, Dongfang; Huang, Hanxiao; Cao, Huawen; Li, Youguo; Huang, Yong; Nie, Fei; Song, Wenjie (Geological journal (Chichester, England), 2023)
Due to the lack of corresponding magmatic records, the timing of the opening of the Yarlung–Tsangpo Neo‐Tethyan Ocean remains controversial. The Middle Permian Luerma igneous complex, which is situated in the western Gangdese magmatic belt of the southern Lhasa subterrane, western Tibet, can be divided into four or more rock types, including foid gabbro, amphibole gabbro, monzogabbro, and pyroxene‐bearing monzodiorite. Through zircon U–Pb dating using laser ablation–inductively coupled plasma–mass spectrometry, the age of the Luerma igneous complex is determined to be ~261 Ma. The complex is rich in titanium, iron, magnesium, and total alkalis, with medium to high levels of calcium, potassium and aluminium, as well as low levels of silicon. Therefore, it is classified as a shoshonite–latite rock series. The complex is relatively enriched in light rare earth elements and high‐field‐strength elements, without obvious Eu and Ce anomalies. These rocks exhibit relatively low (87Sr/86Sr)i values, high εNd(t) values, and high εHf(t) values. The geochemical and isotopic characteristics indicate that the magmas are derived from partial melting of the upper mantle in an intraplate tectonic environment. The new data presented here provide supplementary evidence for the initial rifting of the Lhasa terrane from the northern margin of Gondwana during the Middle Permian. These data also confirm that the opening of the Yarlung–Tsangpo Neo‐Tethyan Ocean occurred in the Middle Permian. (a) Simplified tectonic map of the Qinghai–Tibet Plateau, (b) simplified tectonic map of the Lhasa terrane, (c) simplified geological map of the Luerma area.